Post-Birth Custom on Malay People in Jongkong Kapuas Hulu - kartono, kartono (The Pontianak State Institute of Islamic Studies, 2018)
This article discusses the traditional knowledge of society is the wealth of inheritance obtained from previous generations. The knowledge contains two elements; local elements and elements of Islam. In this element there are beliefs that are associated with supernatural powers, and there are also beliefs that are associated with science. Explanation of these two aspects often cannot be done because of a limited understanding of the culture of the community. Instead of culture that is sustainable, often culture is abandoned because it is considered a prohibited work. Taking examples of activities 40 days after giving birth, this article explains the transition of cultural aspects from belief to knowledge. That is why the response to local culture must be preceded by deepening before any attitude is given.